Committee on Junior (Community) College Curriculum. (The Accounting Review, 1973)
The article presents a report of the 1971-1972 Committee on the Junior (Community) College Curriculum of the American Accounting Association (AAA) which provided recommendations to improve cooperation between community colleges and junior colleges. Students generally do not decide to major in accounting until their freshman or sophomore year in college. The number of students who transfer from community colleges to complete the baccalaureate degree with a major in accounting is steadily increasing. Two-year colleges are growing so rapidly that some day they may provide most of the introductory accounting education. The AAA should sponsor workshops, seminars, and/or courses that would acquaint community college teachers with innovative teaching methods as well as the significant concepts developed in recent years. The AAA should step up efforts to attract community college teachers to the regional and national meetings.